Computational studies on thermo-kinetics aspects of pyrolysis of isopropyl acetate and its methyl, bromide and hydroxyl derivatives. Issue 11 (November 2022) - Shojaei, S.H. Reza; Shiroudi, Abolfazl; Abdel-Rahman, Mohamed A.
Abstract: The gas-phase decomposition kinetics of isopropyl acetate (IPA) and its methyl, bromide and hydroxyl derivatives into the corresponding acid and propene were investigated using density functional theory (DFT) with the ω B97XD and M06–2x functionals, as well as the benchmark CBS-QB3 composite method. Transition state theory (TST) and RRKM theory calculations of rate constants under atmospheric pressure and in the fall-off regime were used to supplement the measured energy profiles. The results show that the formation of propene and bromoacetic acid is the most dominant pathway at the CBS-QB3 composite method, both kinetically and thermodynamically. There was a good agreement with experimental results. Pressures greater than 0.01 bar, corresponding to larger barrier heights are insufficient to ensure saturation of the measured rate coefficient when compared to the RRKM kinetic rates. Natural bond orbitals (NBO) charges, bond orders, bond indices, and synchronicity parameters all point to the considered pathways taking place via a homogenous, first-order concerted, as well as an asynchronous mechanism involving a non-planar cyclic six-membered transition state. The calculated data exhibit that the elongation of the Cα −O bond length and subsequent polarization of the Cα +δ …O −δ bond is the rate-determining step of the considered reactions in the cyclic transition state, which appears to be involved in this type of reaction. Abstract : Isopropyl acetates; Pyrolysis; Rate coefficients; DFT; NBO; Reaction mechanisms.